2016
DOI: 10.1017/s1041610216001137
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive leisure activities and future risk of cognitive impairment and dementia: systematic review and meta-analysis

Abstract: There is increasing evidence that participation in cognitively stimulating leisure activities may contribute to a reduction of risk of dementia and cognitive impairment in later life. Promoting involvement in such activities across lifespan could be an important focus for primary prevention strategies for governments and health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
188
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(204 citation statements)
references
References 53 publications
15
188
0
1
Order By: Relevance
“…Also, a stronger relationship of lifestyle with memory, but not with other cognitive functions like for example executive functions [5]. The relevance of lifestyle factors is in line with another meta-analysis [6] showing that cognitively stimulating leisure activities may contribute to a reduced risk of cognitive impairment in later life. Furthermore, some studies show the beneficial effect of music training for cognitive improvement in older adults: Learning to play the piano and to read music improved the executive functions in older adults [7].…”
Section: Commentarysupporting
confidence: 66%
“…Also, a stronger relationship of lifestyle with memory, but not with other cognitive functions like for example executive functions [5]. The relevance of lifestyle factors is in line with another meta-analysis [6] showing that cognitively stimulating leisure activities may contribute to a reduced risk of cognitive impairment in later life. Furthermore, some studies show the beneficial effect of music training for cognitive improvement in older adults: Learning to play the piano and to read music improved the executive functions in older adults [7].…”
Section: Commentarysupporting
confidence: 66%
“…Studies in humans have also demonstrated a link between music training early in life and better auditory processing skills later in life, especially in challenging listening environments (39)(40)(41). Although early training in younger life has been shown to confer enduring neurobehavioral advantages and to contribute to positive brain health benefits sustained into older ages, scientists still incompletely understand the basis of this "cognitive reserve" (42,43). However, higher SOP, the accurate reception of target stimuli in the presence of confusable distractors, and the retained connectional integrity of forebrain systems, all of which were intensely engaged by our simple training task, provide key indices of the measured level of protection that is commonly attributed to this "reserve" (2,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Although early training in younger life has been shown to confer enduring neurobehavioral advantages and to contribute to positive brain health benefits sustained into older ages, scientists still incompletely understand the basis of this "cognitive reserve" (42,43). However, higher SOP, the accurate reception of target stimuli in the presence of confusable distractors, and the retained connectional integrity of forebrain systems, all of which were intensely engaged by our simple training task, provide key indices of the measured level of protection that is commonly attributed to this "reserve" (2,43,44). Our results, together with those of others (37)(38)(39)(40)(41), therefore indicate that cognitive reserve may be amplified at any age, that the functional and physical impacts of this amplification can be long enduring, and that with appropriate training dosing, brain health and function is likely sustainable, at a high level, across the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that older adults who rarely participated in mental or social activities had a higher risk of cognitive decline . A high level of social interactions is beneficial for maintaining cognitive function, and participating in a diversity of activities can reduce the mortality of dementia .…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have comprehensively proved that non‐physical leisure activities were mostly cognitively stimulating leisure activities, and cognitive leisure activities mainly included reading books or newspapers, watching TV, listening to music, playing a musical instrument, playing bridge or cards, surfing the Internet, solving crossword puzzles, working in the garden, visiting friends, participating in social activities and so on . Frequently taking part in individual cognitively stimulating leisure activities is associated with a significantly reduced risk of cognitive impairment for older adults . Most studies have grouped leisure activities into physical, mental or intellectual and social components .…”
Section: Introductionmentioning
confidence: 99%